Efficacy of Women Counselors in Mitigating Religious Violent Extremism in Families in the East Bandung Area - Ati, Ati (International Journal of Nusantara Islam, 2025)
This study explores the efficacy of female religious counselors in mitigating religious-based violent extremism within the domestic sphere, focusing on East Bandung—an area with a high susceptibility to radicalization. Employing a qualitative descriptive approach, data were collected through participatory observation, in-depth interviews, and documentation of field activities conducted by female religious counselors. The findings reveal that these counselors adopt a feminine da’wah strategy rooted in empathy, dialogue, and everyday narratives, which significantly contributes to building critical awareness, behavioral transformation, and ideological resilience within families and grassroots communities. Their performance demonstrates competency across Bloom's cognitive, affective, and psychomotor domains, allowing for the effective transmission of moderate religious values and the cultivation of tolerant attitudes. Despite their strategic role, these women face structural challenges, including patriarchal resistance, limited access to specialized deradicalization training, and a lack of institutional support. The study contributes theoretically to discourses on gender, religious communication, and community-based security, highlighting female counselors as transformative agents in the fight against extremism. Practically, it underscores the necessity of integrating gender-sensitive policies in national counter-extremism strategies and calls for formal recognition and empowerment of female religious counselors as vital actors in promoting peace, inclusivity, and social resilience.